(untitled) (CIPEEX, 2026)
Introduction: Obesity is a global public health problem and is associated with several complications, including obesity hypoventilation syndrome (OHS), characterized by daytime hypercapnia and respiratory alterations related to excess weigh1,3,4. Continuous positive airway pressure (CPAP) is considered the main intervention for these patients, with the potential to improve gas exchange and quality of life5,6. Objective: To review the scientific literature on the efficacy of CPAP treatment in individuals with obesity and concomitant OHS. Materials and Methods: This is a literature review conducted in the MEDLINE database (via PubMed) between August and September 2025, including studies published from 2015 to 2025, using the Medical Subject Headings (MeSH) terms: "obesity" and "CPAP," combined with the Boolean operator "AND," through the “[title]” option in the advanced search. Results: Three studies were selected (two clinical trials and one pilot study) that investigated the application of CPAP in different contexts. The results showed that most patients maintained adequate daytime PaCO₂ levels and exhibited clinical stability, even in cases of initial titration failure. Furthermore, CPAP was well accepted by participants, demonstrating efficacy comparable to non-invasive ventilation, with better cost-effectiveness. Conclusion: CPAP is an effective, safe, and cost-efficient therapeutic option for individuals with obesity-associated OHS, contributing to improved respiratory function and maintenance of clinical stability.